A NEW SPORADOTRAGUS (BOVIDAE, MAMMALIA) FROM THE LATE MIOCENE OF BULGARIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
We provide a systematic revision of the late Miocene caprine genus Sporadotragus Kretzoi, 1968, the type-species of which was described from Samos under the specific epithet schafferi. It is distinct from the poorly known Pseudotragus. Some specimens from Samos are rather distinctive, but the whole morphological variation there encompasses that of Palaeoryx parvidens from Pikermi, and we follow earlier authors in considering the two names as synonymous. New material from two late Miocene localities of south-western Bulgaria, Kalimantsi and Strumyani, is referred to a new species, S. vasili, which is more primitive than the Greek one in some skull features, but not in the horn-core morphology.
Keywords: Mammalia; Bovidae; Systematics; late Miocene; Turolian; Bulgaria; Balkano-Iranian province